The Efficacy of MALL Instruction in Business English Learning - Khan, Raja Muhammad Ishtiaq; Noor Raha, Mohd Radzuan; Alkhunaizan, Abdulmohsin Suliman; Mustafa, Ghulam; Khan, Imran (International Association of Online Engineering, 2019)
The existing technological expansion has transformed pervasive revolutions in modern civilization, with continuing innovation of services and products. Nowadays people are having different channels of communication. Currently, mobile learning (M-learning) is being used extensively in teaching and learning foreign languages which further widens the mobility of learners. The usage of mobile instruction can lead learners towards a real interruption to learn effectively when used inappositely. The current study is an attempt to explore the potential usage of M-Learning in English for specific purpose (ESP) classes. For this intention smartphone were used in the ESP context for teaching Business English at the College of Business Administration at a public sector university in Saudi Arabia. A questionnaire was distributed to 21 participants of the present study after a 5-week exposure to M-learning activities in the formal classroom. The findings revealed that ESP learners acknowledge M-learning as a prompt source of feedback in ESP. The results of this study also indicate that incorporation of M-learning in ESP learning with conventional classroom can support learners to develop their learning proficiency. Moreover, learners showed significantly positive attitude in mobile instruction in a formal classroom.